Revisiting the former approach: Low-dose dopamine in kidney transplant recipients - VELİOĞLU, ARZU; AŞICIOĞLU, EBRU; ARIKAN, İZZET HAKKI; ŞENTÜRK DURMUŞ, NURDAN; YEGEN, ŞEVKET CUMHUR; TUĞLULAR, ZÜBEYDE SERHAN (MARMARA UNIV, FAC MEDICINE, 2021)
Objective: We aim to evaluate the effects of low-dose dopamine (LDD) infusion (0.5 - 2.5 g/kg/m) on hemodynamic status and short-term graft function in kidney transplant recipients. Materials and Methods: Patients who underwent kidney transplantation surgery between January 2007 and December 2016 were included in the study. Demographic and laboratory data, presence of delayed graft function, and the rates of rejection, graft loss, and mortality were recorded. The data were compared between patients with and without LDD treatment. Results: A total of 126 patients were included in the study (M/F:50.8%/49.2%; mean age, 38.94 +/- 11.8 years). Ninety-four patients (74.6%) received living-donor transplants. Fifty-seven patients underwent LDD infusion in the postoperative period (LDD group), while 69 patients did not receive LDD infusion. Demographic and laboratory data of the patients did not significantly differ between groups. Nineteen patients in the LDD group experienced delayed graft function (p=0.039). However, these patients tended to be older, have a longer dialysis period prior to transplantation, deceased and hypertensive donors. There was no significant difference in renal function at 6 months after transplantation between groups. Conclusion: Although, LDD infusion increases kidney blood flow, we observed no significant effects on short-term graft function or patient survival between the LDD and non-LDD groups.
Keywords: DELAYED GRAFT FUNCTION; IMPACT